2021
DOI: 10.3389/fpubh.2021.670082
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Risk of Hospitalization With Stronger Community Belonging Among Aging Canadians Living With Diabetes: Findings From Linked Survey and Administrative Data

Abstract: Background: Social isolation has been identified as a substantial health concern in aging populations, associated with adverse chronic disease outcomes and health inequalities; however, little is known about the interconnections between social capital, diabetes management, and hospital burdens. This study aimed to assess the role of community belonging with the risk of potentially avoidable hospitalization among aging adults living with diabetes in Canada.Methods: The study leveraged a novel resource available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…From the above, we decided that it was appropriate to dichotomize the groups in subsequent multiple logistic analysis. The mean ± SD (range) of CCS scores was 17.2 ± 3.7 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) for the total participants, 18.4 ± 3.2 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) for leaders, and 17.2 ± 3.8 (7-24) for members. We set a cutoff of 17/18 for the overall analysis, 18/19 for the analysis of leaders, and 17/18 for the analysis of members, based on the mean CCS scores: 17.2 (total; n = 926), 18.4 (leaders; n = 54), and 17.2 (members; n = 872) among study participants (Table 3).…”
Section: Dependent Variablementioning
confidence: 96%
See 1 more Smart Citation
“…From the above, we decided that it was appropriate to dichotomize the groups in subsequent multiple logistic analysis. The mean ± SD (range) of CCS scores was 17.2 ± 3.7 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) for the total participants, 18.4 ± 3.2 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) for leaders, and 17.2 ± 3.8 (7-24) for members. We set a cutoff of 17/18 for the overall analysis, 18/19 for the analysis of leaders, and 17/18 for the analysis of members, based on the mean CCS scores: 17.2 (total; n = 926), 18.4 (leaders; n = 54), and 17.2 (members; n = 872) among study participants (Table 3).…”
Section: Dependent Variablementioning
confidence: 96%
“…When this need goes unmet, it can not only serve as the basis for problems such as social isolation [7], crime, and accidents in the community [8][9][10][11], but serious impacts on the internal lives of older individuals, which are not visible from the outside, can occur, such as effects on their dignity. Additionally, a low sense of belonging together with low community commitment can result in declining health [12][13][14][15] and may even result in early death [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Sense of belonging is described as a “component of connecting one's self into the fabric of surrounding people, places, and things” ( 12 ). While feelings of belonging have been investigated among various populations (e.g., young adults, older adults, and patients) ( 9 , 13 , 14 ), limited studies have examined the sense of belonging felt by caregivers. Furthermore, paid and unpaid caregivers may have different needs, preferences, and barriers related to connecting with their community and interpersonal groups; however, limited studies have examined or compared feelings of social support or sense of belonging among paid and unpaid caregivers ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…46(p1394) Studies have shown that community belonging can act as a proxy indicator for social support 47 and thereby enhance various health outcomes. [47][48][49][50][51] Furthermore, multiple studies have confirmed the stress-buffering role of community belonging among immigrants and racial/ethnic minority populations. [52][53][54][55][56] Applied to the present scenario, a strong sense of community connectedness could provide a less stigmatized living environment for sexual minority individuals, facilitating more positive identity development.…”
mentioning
confidence: 98%